Tolerability and efficacy of durvalumab in Japanese patients with advanced solid tumors. Issue 5 (13th April 2019) - Fujiwara, Yutaka; Iguchi, Haruo; Yamamoto, Noboru; Hayama, Manabu; Nii, Masahiro; Ueda, Shinya; Komuro, Keiko; Sugimoto, Mariko; Vlahovic, Gordana; Kozuki, Toshiyuki
Abstract : Blockade of programmed cell death ligand‐1 with durvalumab has shown efficacy and safety in large, international studies of patients with advanced solid tumors. A phase 1, non‐randomized, open‐label multicenter study was initiated to evaluate durvalumab in a Japanese population. The first part of this study used a standard 3 + 3 dose‐escalation design to determine the optimal dosing schedule of durvalumab. Primary objective was evaluation of safety and tolerability of durvalumab monotherapy. Secondary objectives were to evaluate maximum tolerated dose (MTD), immunogenicity, pharmacokinetics, and efficacy. Twenty‐two patients (median age, 61.5 years; range, 41‐76; 64% male) received durvalumab at doses of 1, 3, or 10 mg/kg every 2 weeks (q2w), 15 mg/kg q3w, or 20 mg/kg q4w. Twenty patients discontinued before completing 12 months of treatment as a result of progressive disease and two due to adverse events (AE). The most common treatment‐related AE (trAE) were rash (18%) and pruritus (14%); two patients had grade ≥3 trAE including one patient each with hyponatremia and hypothyroidism. No patient experienced a dose‐limiting toxicity (DLT) during the DLT evaluation period and the MTD was not identified. There were no AE leading to a fatal outcome during study treatment. Durvalumab showed dose‐proportional pharmacokinetics across the 1‐20 mg/kg dose range; incidence of positive titers for antidrug antibodies was 9%. One patient with lung cancer had a partial response and disease control rate at 12 weeks was 36%. In conclusion, durvalumab at the doses and regimens evaluated was safe and well tolerated in Japanese patients with advanced solid tumors.